Універсальна особистість як феномен музичної культури: доба ренесансу - Коменда, Ольга Іванівна; Komenda, Olha I. (Тернопільський національний педагогічний університет імені В. Гнатюка, 2016)
У статті розглянуто феномен універсальної творчої особистості в контексті музичної культури епохи Ренесансу. Висвітлено основні постаті італійської, французької, нідерландської, іспанської музичної культури ХIV‒XVI століть з позицій взаємодії різних способів їхньої творчої реалізації. Здійснено спробу виявити вплив основних видів діяльності музикантів ‒ композиції, виконавства, музикознавства ‒ на формування цілісної творчої індивідуальності. The phenomenon of universal creative personality in the context of the musical culture of the Renaissance is revealed in this paper. The basic figures of Italian, French, Dutch, Spanish musical culture of XIV‒XVI centuries to the interaction of different ways their creative implementation are described. The impact of the main types of musician’s ‒ composition, performance, musicology ‒ on the formation of a coherent artistic personality is attempted to identify. Modern psychologists view a personality as a complex phenomenon and multifaceted system that has an individual nature. According to them a personality revealed through the individual activity. The problem of universal personality has its own specifics. Its origin caused of historical, national and individual psychological factors. The principles of universalism in the Renaissance, in comparison with the Middle Ages, was much entrenched. This is due to the empowerment of selfidentity. When study the biographies of famous composers of those time, it is impossible not to notice the diversity realization of their creative genius. It was the mandatory combination of performance and compositional activity. It combined labor writer, musician and scientist too. In the history of music examples of such combinations are very much. The main ones are described in this paper. The Renaissance artist was also a composer, head of concert life at court and organizer of music in Church. He had to meet all the artistic needs of their owners. Nobles or the clergy were “clients” of all musical events. Thus the dependence of the artist from the “employer” has stimulated the versatility of the latter. The many interests and activities are closely intertwined with each other. This makes it impossible to distinguish among them principal and derivatives species. One reason for this is the current incomplete of biographical information.The author has identified the following features of the universal creative personality of the Renaissance: 1) the performing activities quantitatively and qualitatively dominated over all others; the composer creativity served for creative interests and needs of the performing work; the musician recognition led to its recognition of the virtuoso performer, this practice is preserved even partially in the nineteenth century; 2) the differentiation of activities of musician was insignificant; there is a close relationship between activities; forms of activities are not aware of their carriers as separate, but perceived as an indivisible whole; 3) specializations of performer-vocalist and performer-instrumentalist were absent; trend of mixing of the different types of performing and various skills has dominated; often the musician had another specialty (a poet, a philosopher, a mathematician, a lawyer, a diplomat); 4) the creative work “on demand” was widespread; creative ideas fueled of the practical needs of the court, or church service; 5) the phenomenon of universalism of creative person was in a syncretistic «immature» state; the combining of the two activities ‒ a performance and a composition ‒ was in the basis of universal personality of Renaissance musician; the adding to their of academic activities encountered much less frequently.
The universal personality as a phenomenon of renaissance music culture
Keywords: універсальна творча особистість; композиція; виконавство; музикознавство; музична культура доби Ренесансу; universal creative personality; composition, performance; musicology; music culture of the Renaissance